Effective Use of Computer Graphics in CAI: A Review of the Literature (Vol15, No. 2, 1986) - Siliauskas, Gina (Canadian Journal of Learning and Technology, 2009)
This is a reprinted version of an article from Vol. 15 No. 2. You can view the original here.